Revolution for Digitalization of Agriculture in India: A Comprehensive Study - Shivam Satyawan Madrewar; Sangeeta Dhinwa; Atharva Manish Gumphekar; Prathamesh Balasaheb Tavhare; Om Vijay Suryawanshi; Ajay Rajaram Sagar (International Journal of Global Sustainable Research, 2024)
The role of digitalization in ensuring food security through optimized resource management and distribution is examined, alongside the integration of AI, Machine Learning, and IoT in agricultural education and management, especially under the National Education Policy 2020. The study also covers advancements in cattle health and livestock management, precision agriculture in fruit cultivation, and the role of Krishi Vigyan Kendras (KVKs) in digitally supporting farmers. Additionally, it discusses the promotion of natural and organic farming practices through initiatives like Paramparagat Krishi Vikas Yojana (PKVY) and the growth of digital marketplaces for organic produce. By synthesizing data from various sources, the paper provides a comprehensive overview of India’s digital agriculture landscape, underscoring its contribution to a more sustainable and productive sector and positioning India as a global leader in digital agriculture.